2021
DOI: 10.1111/and.14252
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Rosmarinus officinalis on orchitis following spermatic cord torsion‐detorsion in male mice with emphasis on anti‐ inflammatory and antioxidant properties

Abstract: Testes are the male sex mammalian organs that are involved in the production of spermatozoa and sex hormones. During fertilisation, the healthy spermatozoa could fertilise the egg to form a zygote. Besides, Testosterone (Tes) is secreted by Leydig cells, promotes secondary sexual characteristics and preserves proper testicular function (Guazzone et al., 2009). Production of healthy spermatozoa along with testosterone secretion is all possible in the presence of healthy testes with no pathological changes such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…H&E staining was used for histopathological assessments of slides according to various protocols of deparaffinization, hematoxylin staining, alcoholic‐eosin staining, acid‐alcoholic administration, and xylene‐based clearing. Seminiferous tubule, interstitial tissue, lumen, and spermatogenic cell lines were observed microscopically (40×) 14 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…H&E staining was used for histopathological assessments of slides according to various protocols of deparaffinization, hematoxylin staining, alcoholic‐eosin staining, acid‐alcoholic administration, and xylene‐based clearing. Seminiferous tubule, interstitial tissue, lumen, and spermatogenic cell lines were observed microscopically (40×) 14 …”
Section: Methodsmentioning
confidence: 99%
“…Seminiferous tubule, interstitial tissue, lumen, and spermatogenic cell lines were observed microscopically (40×). 14 …”
Section: Methodsmentioning
confidence: 99%
“…At present, few studies have focused on characterizing the anti-inflammatory and antioxidant effects of Rosmarinus officinalis extracts. For instance, it has been demonstrated that rosemary extracts are effective in the treatment of orchitis by exerting an antioxidant effect on murine sperm [ 62 ]. Likewise, a polyherbal formula based on Populus nigra L. and R. officinalis extracts demonstrated a therapeutic potential for diseases based on oxidative stress and inflammation [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, several biological studies have reported that rosemary extract possesses anti‐inflammatory properties by significantly inhibiting cyclooxygenase‐2 (COX‐2) (Pereira et al., 2023). In addition, the inhibitory activities of the rosemary extract toward tumor necrosis factor (TNF)‐ α , interleukin (IL)−1 β , IL‐6, IL‐10, prostaglandin E 2 , inducible nitric oxide synthase (iNOS), toll‐like receptor 4, myeloperoxidase (MPO), catalase, glutathione, glutathione peroxidase, malondialdehyde, and superoxide dismutase were also widely evaluated (Goncalves et al., 2022; Khalid et al., 2020; Torghabeh et al., 2022), implying that rosemary extracts might be applied as a wide spectrum of anti‐inflammatory agents with various protein targets.…”
Section: Biological Activities Of Rosemary Extractmentioning
confidence: 99%